Development of Islamic libraries : a Malaysian perspective - Suja', Balqis (2008)
The purpose of this paper is to give focus on the evolution of Islamic libraries into a specialization which has not received much attention in the literature. This paper provides a brief overview on Islamic libraries, its historical background, development and prospects. A literature survey is used to describe characteristics of Islamic libraries and identifying topics for gauging awareness on Islamic libraries requirements and strategy for its development. Selected topics and issues include perspective on the services and collections, organization and access, professionalization of Islamic librarianship, and impact of technology on Islamic libraries. What follows are ideas to embrace and promote Islamic libraries as a specialization by noting issues and problems faced by Islamic libraries, current challenges and direction for research. Discussion on Malaysian scenario relevant to Islamic libraries development is supplemented with an appendix of a list of Islamic libraries in Malaysia at the end of this paper.